Policy Formulation Of Expansion And Change Status Of Kelurahan To Village In Kampar District Riau Province (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This research departs from the many wishes of the kelurahan community to propose regional expansion. The Kampar Regency Government also gave a good response to follow the public's wishes. However, in the process of the due diligence team found several problems in the field, including the discovery of several villages whose administrative requirements had not been completed, especially the insufficient population, namely the minimum number of 5000 people or 1000 households, then there were several sub-districts where the administrative area boundaries between Kelurahan expansion with the main sub-district and of course this involves 2 interests between the community leaders of the main village and community leaders of the pemekaran village, several sub-districts that will apply for regional expansion do not want to expand their territory to become sub-districts but will immediately become villages while the legal basis governing the division of parts of the sub-district area which immediately became a village, there were no regulations issued either by the Ministry of Villages or by the Ministry of Home Affairs. This research method will be carried out using a qualitative research method with a descriptive type because empirically this research problem is more appropriately studied using a qualitative approach. The results of the study show that the process of determining the policy agenda for dividing sub-districts into villages in Kampar Related district regarding the formulation of the policy agenda for dividing sub-districts into villages, when viewed from the regulations governing the division of sub-districts into villages in outline contains the importance of reviewing legal aspects. Because indeed regulations have not been specifically regulated regarding the division of sub-districts into new villages, there are only government regulations regarding sub-districts or government regulations regarding village division. So that the team involved in the expansion of the area found a dead end from the problems found in the field. Keywords: Collaborative Governance, Tourism Object Development, Tourism
Keywords: Collaborative Governance, Tourism Object Development, Tourism